Noyau of the Krakow fortress in the second half of the 19th century - Opaliński, Piotr (City and War, 2021)
In 1857 the Austrian military authorities started building an internal line of defence in the Krakow fortress, known as Noyau. Krakow, as an extremely important strategic point on the map of the Habsburg monarchy, required urgent fortification. The works were preceded by field studies and considerations of several variants of the planned fortifications. In progress, obstacles appeared which caused completion of the investment only after 9 years. The construction of Noyau, permanently saved in the history of the city, affected its urban planning and spatial development. Despite the demolition of most of the fortifications, we can still see a trace of their presence in the form of a system of communication routes, surrounding today’s downtown of Krakow.